Development of a professional orientation educational event on the topic “The world of professions in historical retrospective” (Actual Problems of Psychology in Educational Institutions, 2023)
The article presents practical aspects in career guidance work.The highlighted materials will be useful for teachers working with highschool students. Practical recommendations are provided for covering thetopic of career guidance in terms of interdisciplinary connection with historyand psychology. The practical aspect of the development of schoolchildren’scritical thinking through the format of group work is outlined. Techniquesfor working with spatial thinking and the skills of analyzing historicalevents are provided. The connection between various professions and thechange of historical events in the process of building human society ispresented. The idea of career guidance work in the format of practicaldevelopment of an educational event for high school students is revealed
Keywords: career guidance, critical thinking, historical eras, professional definition